Angiographic severity in acute coronary syndrome patients with and without standard modifiable risk factors - Papazoglou, Andreas S.; Farmakis, Ioannis T.; Zafeiropoulos, Stefanos; Moysidis, Dimitrios V.; Karagiannidis, Efstratios; Stalikas, Nikolaos; Kartas, Anastasios; Stamos, Konstantinos; Sofidis, Georgios; Doundoulakis, Ioannis; Giannopoulos, Georgios; Giannakoulas, George; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Routine coronary artery disease (CAD) secondary prevention strategies target standard modifiable cardiovascular risk factors (SMuRFs), namely diabetes mellitus, dyslipidemia, hypertension and smoking. However, a significant proportion of patients with acute coronary syndrome (ACS) present without any SMuRFs. The angiographic severity of disease in this population has not yet been investigated. Methods: After propensity score matching of patients without SMuRFs and patients with ≥1 SMuRFs (ratio 1:3), we used zero-inflated negative binomial regression modeling to investigate the relationship of SMuRF-less status with the angiographic severity of CAD, as measured by the SYNTAX score. Survival analysis was performed to investigate differences in all-cause mortality at 30 days and at the end of follow-up period. Results: We analyzed 534 patients presenting with ACS who underwent coronary angiography. Of them, 56 (10.5%) presented without any SMuRF. After propensity score matching, the median SYNTAX score was 13.8 (IQR 0-22.1) in 56 SMuRF-less patients and 14 (IQR 5-25) in 166 patients with ≥1 SMuRFs. SMuRF-less status was associated with increased odds of zero SYNTAX score [zero-part model: odds ratio = 2.11, 95% confidence interval (CI): 1.03-4.33], but not with decreased SYNTAX score among patients with non-zero SYNTAX score [count-part model: incidence rate ratio = 0.99, 95% CI: 0.79-1.24]; the overall distribution of the SYNTAX score was similar between the two groups (p=0.26). The 30-day risk for all-cause mortality was higher for SMuRF-less patients compared to patients with ≥1 SMuRFs [hazard ratio (HR) = 3.58, 95% CI: 1.30-9.88]; however, the all-cause mortality risk was not different between the 2 groups over a median 1.7-year follow-up (HR=1.72, 95% CI: 0.83-3.57). Conclusions: Among patients with ACS, the absence of SMuRFs is associated with increased odds for non-obstructive CAD and with increased short-term mortality rates.